Sintesis Butil Sinamat dari Sinamaldehid pada Minyak Kayu Manis (Cinnamomum cassia) dan Uji Aktivitas sebagai Antidiabetes - Fajriyah, Amalia Fitriyan; , S.Si., M.Si., Ngadiwiyana; , M.Si, Dra. Dewi Kusrini (Chem Info Journal, 2013)
Diabetes Millitus (DM) is a metabolic disorder characterized by high blood sugar levels. Cinnamon oil has an antidiabetic potential. Cinnamaldehyde is the main component of cinnamon oil (78 %) containing of aldehyde group which can be modified into the ester group is expected to be potentially as an antidiabetic. The purpose of this research was to isolate cinnamaldehyde from cinnamon oil, cinnamaldehyde oxidation became cinnamic acid, butyl cinnamate synthesis from cinnamic acid and activities test of butyl cinnamate as an antidiabetic. The method of this research was oxidation and esterification. Butyl cinnamate obtained from the synthesis is orange-yellowish liquid and fragrant smell with it’s yield as big as 97,79 %. The result of FTIR shows that it has been formed butyl cinnamate with absorption of ester (C-O), whereas the results obtained by GC-MS is an abundance of butyl cinnamate as big as 100 %. The result of the antidiabetic test, butyl cinnamate have IC50 value as big as 120,951 ppm.